COMPARISON OF THE EFFECTIVENESS OF RELATIVE VALUATION RATIOS (PE AND PBV) IN PREDICTING SHARE PRICES BOOK IV BANKING AND DIGITAL BANKS - Apriwandi Apriwandi; Debbie Christine (SEAN Institute, 2023)
Valuation of a share is something that must be done by every investor in order to know the fair value of the share. Currently there is a digital bank industry that is booming where the share price is quite high compared to the share price of ordinary banks, so this study aims to assess the share price of digital banks compared to ordinary banks using the relative valuation method with PER and PBV ratios and analyzed using panel data analysis to determine the effectiveness of the valuation. The results of this study prove that the relative valuation method can be used and is quite effective for valuing the shares of digital banks and ordinary banks.